Pathophysiology, diagnosis and treatment of neonatal sepsis. (28th August 2014) - Dunkel, B.; Corley, K. T. T.
Summary Sepsis is a major cause of death in neonatal foals and, in recent years, significant progress in the understanding of the underlying pathophysiology has been made. To achieve a successful outcome, early diagnosis and treatment focusing on supporting vital functions and neutralising the effects of the causative organisms are essential. The pharmacokinetics of many drugs differ in neonatal foals and more information for appropriate dosing of antimicrobial and anti‐inflammatory drugs for neonatal foals is now available to guide clinicians in choosing the best dosages. Prevention remains difficult and focuses on early recognition while prophylactic use of antimicrobials is discouraged.